El pensamiento antiutilitarista y la decolonialidad en las Ciencias Sociales: la continuación del MAUSS en una revista latinoamericana. - Soto-Acosta, Willy (2014)
The work focuses on the “Revista de Estudos AntiUtilitaristas e PosColoniais” (REALIS) magazine, a publication that is made in Brazil and aims to articulate the anti-utilitarian thought born in France with the theory of the coloniality of power emerged in Latin America. The magazine is a scientific production effort for political purposes, which rescues both theoretical reflection itself of the South as North critical approaches. REALIS is, to the author, an example of how to overcome the "complicity of Social Sciences with the coloniality of power" and how serious scientific research, based, can have a very clear political purpose.